B1 I CO DALEJ? O KONIECZNOŚCI PRZYGOTOWANIA PROGRAMU NAUCZANIA JĘZYKA POLSKIEGO JAKO OBCEGO DLA CELÓW AKADEMICKICH - Jasińska, Agnieszka (Neofilolog, 2019)
For the past several years we have been observing a substantial growth of interest in studies in Poland among foreign students, particular those from the East. The required level of language proficiency for Polish universities is B1 which is not difficult to achieve in a year. It is, however, by no means sufficient to participate in university classes, to follow academic discourse, to write papers or prepare for exams. This article presents the results of a research study conducted among academic lecturers and Polish language instructors teaching preparatory classes on the lacks and needs of foreign students. It also presents core demands regarding teaching Polish as a foreign language for academic purposes.